2002
DOI: 10.1590/s0100-41582002000100012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phaeoisariopsis griseola pathotypes from five States in Brazil

Abstract: Due to the increased importance of angular leaf spot of common bean (Phaseolus vulgaris) in Brazil, monitoring the pathogenic variability of its causal agent (Phaeoisariopsis griseola) is the best strategy for a breeding program aimed at developing resistant genotypes. Fifty one isolates of P. griseola collected in five Brazilian States were tested on a set of 12 international differential cultivars in the greenhouse. When inoculated plants showed symptoms but no sporulation was observed, they were transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 3 publications
7
19
1
9
Order By: Relevance
“…This demonstrates that it is necessary to obtain cultivars with resistance genes from both gene pools in order to obtain durable resistance (Miklas et al, 2006). The cultivars Cornell 49242 and AND 277 exhibited a moderate level of resistance, in contrast with other studies that have found a high level of resistance in these cultivars (Busogoro et al, 1999;Sartorato, 2002). Therefore, the results of the present study lay emphasis on high aggressiveness of strains used in comparison with the previously cited studies.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This demonstrates that it is necessary to obtain cultivars with resistance genes from both gene pools in order to obtain durable resistance (Miklas et al, 2006). The cultivars Cornell 49242 and AND 277 exhibited a moderate level of resistance, in contrast with other studies that have found a high level of resistance in these cultivars (Busogoro et al, 1999;Sartorato, 2002). Therefore, the results of the present study lay emphasis on high aggressiveness of strains used in comparison with the previously cited studies.…”
Section: Discussioncontrasting
confidence: 54%
“…The existence of races is a complication in breeding programs, because cultivars may be resistant to certain races and susceptible to others. P. griseola has great variability, which explains the large number of existing races and the complexity of genetic resistance (Mahuku et al, 2002;Sartorato, 2002;Damasceno-Silva et al, 2008). In addition, in Brazil, most of the strains have been classified as race 63.63, which overcomes the resistance of all the cultivars of the differential group (Balbi et al, 2009;Pereira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the study of inheritance was based on only one parental cross. However, it should be noted that the occurrence of different breeds of angular leaf spot has been reported in the literature (Sartorato, 2002;Sartorato and Alzate-Marin, 2004). Amaro et al (2007) reported a gradation in symptoms among lines considered susceptible to angular leaf spot, and suggested that part of this gradation can be attributed to environmental effects and the polygenic control of the trait, because resistance to angular leaf spot has a complex inheritance.…”
Section: Estimates Of Gca and Sca In Relation To Alsmentioning
confidence: 99%
“…Crous and U. Braun is one of the most important and widely distributed diseases of common bean (Phaseolus vulgaris L.) in producing regions (Sartorato and Alzate-Marin, 2004;Damasceno-Silva et al, 2008). Breeding for resistance has found some difficulties due the great pathogenic variability and absence of genetic control information for some lines (Sartorato, 2002). Information about genetic control is very useful, because it helps breeders to choose the most efficient strategies to make it possible to obtain resistant and productive cultivars.…”
Section: Introductionmentioning
confidence: 99%